Endoscopic Insufflation–Induced Gastric Barotrauma during Percutaneous Endoscopic Gastrostomy: A Report of Three Patients and Review of Literature - Seth, Avnish Kumar; Bansal, Rinkesh Kumar (Journal of Digestive Endoscopy, 2021)
Background We report three patients with endoscopic insufflation–induced gastric barotrauma (EIGB) during upper gastrointestinal endoscopy (UGIE) for percutaneous endoscopic gastrostomy (PEG). A definition and classification of EIGB is proposed.Materials and Methods Records of patients undergoing UGIE over 7 years (April 2013–March 2020) were reviewed. Patients who developed new onset of bleeding or petechial spots in proximal stomach, in an area previously documented to be normal during the same endoscopic procedure, were studied.Results New onset of bleeding or petechial spots in proximal stomach occurred in 3/286 (0.1%) patients undergoing PEG and in none of the 19,323 other UGIE procedures during the study period. All patients were men with median age 76 years (range 68–80 years), with no coagulopathy. Aspirin and apixaban were discontinued 1 week and 3 days prior to the procedure. Fresh blood was noted in the stomach at a median of 275 seconds (range 130–340) seconds after commencement of endoscopy. At retroflexion, multiple linear mucosal breaks of up to 3 cm, with oozing of blood, were noted in the proximal stomach along the lesser curvature, close to the gastroesophageal junction in two patients. In the third patient, multiple petechial spots were noticed in the fundus. The plan for PEG was abandoned and the stomach deflated by endoscopic suction. There was no subsequent hematemesis, melena, or drop in hemoglobin. One week later, repeat UGIE in the first two patients revealed multiple healing linear ulcers of 1 to 3 cm in the lesser curvature and PEG was performed.Conclusion Overinsufflation over a short duration during UGIE may lead to EIGB. Early detection is key and in the absence gastric perforation, patients can be managed conservatively.
Keywords: gastric barotrauma; endoscopic insufflation–induced gastric barotrauma; complications of endoscopy; complications of percutaneous endoscopic gastrostomy